Promising blockchain applications for agriculture - Janssen, Sander; Bolt, Jaclyn (Technical Centre for Agricultural and Rural Cooperation, 2018)
Sander Janssen and Jaclyn Bolt discuss the potential of blockchain technology for agricultural development by way of multiple exampls, arguing that it needs to be combined with a strategy for digitisation, targeted capacity building of its users and an impact-driven approach.